2015
DOI: 10.1093/neuonc/nov266
|View full text |Cite
|
Sign up to set email alerts
|

Different spatial distributions of brain metastases from lung cancer by histological subtype and mutation status of epidermal growth factor receptor

Abstract: Background. The purpose of this study was to test the hypothesis that the genetic backgrounds of lung cancers could affect the spatial distribution of brain metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 34 publications
(31 reference statements)
6
71
4
Order By: Relevance
“…In the case of lung cancers, brain lesions are typically multiple and disseminated, although interestingly, they do tend to localize in different regions of the brain than other cancer types- a fact that can have diagnostic significance. Specifically, lung cancer metastases to the brain tend to develop focal lesions in “watershed” regions of the brain- these are the regions where the vasculature is finest and most narrow (Takano et al, 2016). This suggests a potential role for hematogenous spread of lung tumor cells to the brain and their subsequent entrapment in fine vessels and extravasation into the tissue.…”
Section: Current Clinical Management Of Lung Tumor Brain Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of lung cancers, brain lesions are typically multiple and disseminated, although interestingly, they do tend to localize in different regions of the brain than other cancer types- a fact that can have diagnostic significance. Specifically, lung cancer metastases to the brain tend to develop focal lesions in “watershed” regions of the brain- these are the regions where the vasculature is finest and most narrow (Takano et al, 2016). This suggests a potential role for hematogenous spread of lung tumor cells to the brain and their subsequent entrapment in fine vessels and extravasation into the tissue.…”
Section: Current Clinical Management Of Lung Tumor Brain Metastasismentioning
confidence: 99%
“…Indeed, treatment with these drugs, especially in patients with primary lung disease that demonstrates EGFR mutation shows superior efficacy versus traditional chemotherapies in shrinking brain metastases, with 60–80% response rates (reviewed in (Dempke et al, 2015)). Interestingly, patients with EGFR mutant disease treated with EGFR inhibitors show somewhat different patterns of brain metastasis, including metastases that are less deeply seeded within the brain (Takano et al, 2016). …”
Section: Current Clinical Management Of Lung Tumor Brain Metastasismentioning
confidence: 99%
“…In addition, the median size of the tumors in patients with exon 19 deletion was smaller compared with wild‐type cancers, as was the associated peri‐tumoral edema. Radiographic analysis of 200 patients with brain metastases treated in Japan demonstrated that EGFR L858R was associated with more superficial lesions, preferentially located in the caudate, cerebellum, and temporal lobes compared with exon 19 patients. These data, while still preliminary, suggest that different EGFR mutations may result in somewhat different patterns of CNS metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…29 Another study showed that brain metastases with exon 21 mutations were more common in the caudate, cerebellum, and temporal lobe compared with those with exon 19 deletions. 30 Other characteristic molecular changes of non-small-cell lung cancer are a Kras mutation and Alk rearrangement. 31,32 Patients who were Alk-positive and treated with the Alk TKI crizotinib in the second-line setting experienced improved progression-free survival compared with standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%